Transcriptome-wide identification of optimal reference genes for expression analysis of Pyropia yezoensis responses to abiotic stress - Dong Gao; Fanna Kong; Peipei Sun; Guiqi Bi; Yunxiang Mao (BMC Genomics, 2018)
Abstract Background Pyropia yezoensis, a marine red alga, is an ideal research model for studying the mechanisms of abiotic stress tolerance in intertidal seaweed. Real-time quantitative polymerase chain reaction (RT-qPCR) is the most commonly used method to analyze gene expression levels. To accurately quantify gene expression, selection and validation of stable reference genes is required. Results We used transcriptome profiling data from different abiotic stress treatments to identify six genes with relatively stable expression levels: MAP, ATPase, CGS1, PPK, DPE2, and FHP. These six genes and three conventional reference genes, UBC, EF1-α, and eif4A, were chosen as candidates for optimal reference gene selection. Five common statistical approaches (geNorm, ΔCt method, NormFinder, BestKeeper, and ReFinder) were used to identify the stability of each reference gene. Our results show that: MAP, UBC, and FHP are stably expressed in all analyzed conditions; CGS1 and UBC are stably expressed under conditions of dehydration stress; and MAP, UBC, and CGS1 are stably expressed under conditions of temperature stress. Conclusion We have identified appropriate reference genes for RT-qPCR in P. yezoensis under different abiotic stress conditions which will facilitate studies of gene expression under these conditions.